Overexpression of Wild-Type Human Alpha-Synuclein Causes Metabolism Abnormalities in Thy1-aSYN Transgenic Mice - Cuvelier, Elodie; Méquinion, Mathieu; Leghay, Coline; Sibran, William; Stievenard, Aliçia; Sarchione, Alessia; Bonte, Marie-Amandine; Vanbesien-Mailliot, Christel; Viltart, Odile; Saitoski, Kevin; Caron, Emilie; Labarthe, Alexandra; et al. (Frontiers in Molecular Neuroscience, 2018)
Parkinson’s disease is a progressive neurodegenerative disorder characterized by loss of dopaminergic neurons, pathological accumulation of alpha-synuclein and motor symptoms, but also by non-motor symptoms. Metabolic abnormalities including body weight loss have been reported in patients and could precede by several years the emergence of classical motor manifestations. However, our understanding of the pathophysiological mechanisms underlying body weight loss in PD is limited. The present study investigated the links between alpha-synuclein accumulation and energy metabolism in transgenic mice overexpressing Human wild-type alpha-synuclein under the Thy1 promoter (Thy1-aSYN mice). Results showed that Thy1-aSYN mice gained less body weight throughout life than wild-type mice, with significant difference observed from three months of age. Body composition analysis of 6-month-old transgenic animals showed that body mass loss was due to lower adiposity. Thy1-aSYN mice displayed lower food consumption, increased spontaneous activity, as well as a reduced energy expenditure compared to control mice. While no significant change in glucose or insulin responses were observed, Thy1-aSYN mice had significantly lower plasmatic levels of insulin and leptin than control animals. Moreover, the pathological accumulation of alpha-synuclein in the hypothalamus of 6-month-old Thy1-aSYN mice was associated with a down-regulation of the phosphorylated active form of the signal transducer and activator of transcription 3 (STAT3) and of Rictor (the mTORC2 signaling pathway), known to couple hormonal signals with the maintenance of metabolic and energy homeostasis. Collectively, our results suggest that (i) metabolic alterations are an important phenotype of alpha-synuclein overexpression in mice and that (ii) impaired STAT3 activation and mTORC2 levels in the hypothalamus may underlie the disruption of feeding regulation and energy metabolism in Thy1-aSYN mice.